GENETIC CHARACTERIZATION OF BODY WEIGHT TRAITS IN ROCKY PARTRIDGE CHICKS - Mohammed, Kadhim S.; Al-Barzinji, Yousif M. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The study was conducted on 118 partridges (Alectoris graeca) chicks in order to find the effect of non-genetic factors and genetic evaluation of live weight and carcass of this bird. The results showed a highly significant superiority of the weights of males over females in most age stages (437.71 ± 4.40 vs 375.90 ± 3.66 g/ bird at marketing age) and daily weight gain (ADG) from one day to marketing age (4.70 ± 0.06 vs 4.01 ± 0.04 g/ day/bird). The breeding values (BLUP) ​​of birds for marketing weight ranged from -135.4 g/bird to 56 g/bird. Significant differences were recorded between groups of birds with high and low BLUP values ​​in the average live weight at market (464.21 ± 11.03 vs 352.80 ± 6.47 g/bird) and carcass weight (349.48 ± 7.46 vs 265.91 ± 6.08 g/bird). Males also outperformed females significantly in live weight at marketing and carcass weight. The results also showed a positive and significant correlation between the daily weight gain rate and weights at different ages except for the age on the one day, which were negative and not significant. Also, high correlations were recorded between live body weight at marketing and carcass weight, but the correlation between live weight and dressing ratio was not significant. The wide variation in BLUP values ​​and the presence of high differences between birds with high and low BLUP values ​​indicates the possibility of developing and increasing the weight of these birds through selection and breeding process.